BRCA1 and BRCA2 tumor suppressors protect against endogenous acetaldehyde toxicity. Issue 10 (20th July 2017) - Tacconi, Eliana MC; Lai, Xianning; Folio, Cecilia; Porru, Manuela; Zonderland, Gijs; Badie, Sophie; Michl, Johanna; Sechi, Irene; Rogier, Mélanie; Matía García, Verónica; Batra, Ankita Sati; Rueda, Oscar M; et al.
Abstract: Maintenance of genome integrity requires the functional interplay between Fanconi anemia (FA) and homologous recombination (HR) repair pathways. Endogenous acetaldehyde, a product of cellular metabolism, is a potent source of DNA damage, particularly toxic to cells and mice lacking the FA protein FANCD2. Here, we investigate whether HR‐compromised cells are sensitive to acetaldehyde, similarly to FANCD2‐deficient cells. We demonstrate that inactivation of HR factors BRCA1, BRCA2, or RAD51 hypersensitizes cells to acetaldehyde treatment, in spite of the FA pathway being functional. Aldehyde dehydrogenases (ALDHs) play key roles in endogenous acetaldehyde detoxification, and their chemical inhibition leads to cellular acetaldehyde accumulation. We find that disulfiram (Antabuse), an ALDH2 inhibitor in widespread clinical use for the treatment of alcoholism, selectively eliminates BRCA1/2‐deficient cells. Consistently, Aldh2 gene inactivation suppresses proliferation of HR‐deficient mouse embryonic fibroblasts (MEFs) and human fibroblasts. Hypersensitivity of cells lacking BRCA2 to acetaldehyde stems from accumulation of toxic replication‐associated DNA damage, leading to checkpoint activation, G2/M arrest, and cell death. Acetaldehyde‐arrested replication forks require BRCA2 and FANCD2 for protection against MRE11‐dependent degradation. Importantly, acetaldehyde specifically inhibits in vivo the growth of BRCA1/2‐deficient tumors and ex vivo in patient‐derived tumor xenograft cells (PDTCs), including those that are resistant to poly (ADP‐ribose) polymerase (PARP) inhibitors. The work presented here therefore identifies acetaldehyde metabolism as a potential therapeutic target for the selective elimination of BRCA1/2‐deficient cells and tumors. Synopsis: Treatment with acetaldehyde or with the alcohol‐deterrent disulfiram, which enhances acetaldehyde levels, selectively eliminates BRCA1/2‐deficient cells and tumors. Increasing cellular acetaldehyde might thus benefit cancer patients with BRCA1/2 mutations. Acetaldehyde and disulfiram increased the levels of RPA foci and decreased replication fork progression, leading to accumulation of replication‐associated DNA damage specifically in BRCA2‐deficient cells. The Aldh2 gene encodes an aldehyde dehydrogenase with key roles in endogenous acetaldehyde detoxification. Aldh2 gene deletion or its point mutation E487K associated with the ethanol‐induced flushing syndrome in humans causes proliferation arrest in cells lacking BRCA1/2 expression. Growth of BRCA1/2‐defective tumors, including those that have acquired resistance to PARP inhibitors, is suppressed by acetaldehyde treatment. Abstract : Treatment with acetaldehyde or with the alcohol‐deterrent disulfiram, which enhances acetaldehyde levels, selectively eliminates BRCA1/2‐deficient cells and tumors. Increasing cellular acetaldehyde might thus benefit cancer patients with BRCA1/2 mutations.